Identification of Research Gaps in The Context of Women’sEntrepreneurship in The Arab World - Anggraini, Juwita; Abdul Hamid; Syah, Rizqon Halal Aji; Nofrianto (International Journal of Accounting and Economics Studies, 2025)
This study aims to systematically map the development of research on women’s ‎entrepreneurship in the Arab world and identify key research gaps through a combined ‎systematic literature review (SLR) and bibliometric analysis. Using publications indexed in ‎Scopus, Google Scholar, and Publish or Perish databases from 2015 to 2025, a total of 47 ‎selected articles were analyzed using Biblioshiny and VOSviewer. The findings reveal a significant growth in scholarly attention to women’s entrepreneurship, with research clusters concentrated on socio-economic, political economy, finance, digital entrepreneurship, family and education, and cultural–religious values. However, the literature remains heavily focused on ‎structural barriers such as access to finance, gender norms, and institutional constraints, while ‎strategic dimensions of empowerment, digital resilience, Islamic finance, and sustainability-oriented entrepreneurship remain underexplored. The results also show a geographical ‎concentration in GCC countries, particularly Saudi Arabia and the UAE, with limited ‎representation from non-GCC Arab nations. Furthermore, empirical studies integrating Islamic ‎values, maqasid al-shariah, gender-sensitive financial inclusion, and digital transformation are ‎still scarce. This study contributes by providing a comprehensive mapping of research trends and ‎formulating a structured future research agenda to advance a more inclusive, ethical, and ‎context-sensitive framework of women’s entrepreneurship in the Arab world‎.